The Therapeutic Potential of Curcuma longa (Turmeric) in the Management of Breast Cancer in Female Rats: Mechanisms and Molecular Targets - Qasim, Maytham T.; Thijail, Hayfaa A.; Hameed, Lina A.; Mohammed, Zainab I. (Asian Pacific Journal of Cancer Biology, 2025)
Background: Curcuma longa (turmeric), a traditional medicinal plant, has demonstrated significant antitumor properties in various cancer models. This study investigates the therapeutic efficacy of turmeric extract in the treatment of breast cancer in female rats, focusing on its mechanisms of action and molecular targets. Methods: Female Wistar rats were induced with mammary tumors using 7,12-dimethylbenz [a] anthracene (DMBA). The treated group received standardized doses of turmeric extract orally for six weeks. Tumor volume, histopathological changes, apoptosis markers (e.g., caspase-3), and oxidative stress biomarkers (e.g., MDA, SOD) were evaluated. Results: Rats treated with Curcuma longa showed a significant reduction in tumor size compared to the untreated group (p < 0.05). Histological analysis revealed increased apoptosis and reduced angiogenesis. Molecular assays indicated downregulation of NF-κB and upregulation of p53 expression. Conclusion: Turmeric demonstrated potent antitumor effects in breast cancer–induced rats through modulation of oxidative stress, inflammation, and apoptosis pathways. These findings support further investigation into Curcuma longa as a complementary therapeutic agent in breast cancer management.